Experimental study of the temperature distribution over the surface of a heat supply object under heating conditions with a gas infrared emitter; Journal of Physics: Conference Series; Vol. 1675 : Thermophysics and Physical Hydrodynamics - Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna; Voloshko I. V. Ivan Valentinovich; Gutareva N. Yu. Nadezhda Yurievna (2020, 2020)
Title screen